STRUKTUR MODAL OPTIMAL DALAM MENGHASILKAN LABA UNTUK USAHA KECIL MENENGAH DI KOTA MALANG - Dewi Ratih; MAF. Suprapti (Akubis : Jurnal Akuntansi dan Bisnis, 2019)
This study aims to find out more about the policy of the existing capitalstructure at the Small and Medium Enterprises (SMEs), the influenceof the ratio of debt to assets, the ratio of sales to assets, the loan termto the benefit of business, types of financial institutions, and the loanterm to profitability which measures the continuity of their business.This study is a combination of quantitative research by usingstatistical tests. The qualitative research through general least square(GLS) to test the variable sales to total assets and the ratio of debt tototal assets.The object of research is SMEs spread across the city of Malang byviewing the source of funding and the type of financial institution thatis accessible related to profitability. The sample selection usingpurposive sampling technique with the SME population in the city ofMalang, gained as much as 62 SMEs as the sample population collectedas many as 36 SMEs. The sample is an SME that is included in thepopulation sample that met the selection criteria.The results of the analysis to model 1 shows that the profitability ofSMEs in Malang influenced by the explanatory variables used in thecapital structure research by 74.20% and only range of approximately25% is influenced by other factors. Based on the analysis models II,line of business and the type of financial institution that became thesource of acquisition of capital is not a major factor of financialperformance or profitability of SMEs in Malang.